2018
DOI: 10.1002/mrm.27546
|View full text |Cite
|
Sign up to set email alerts
|

PEC‐GRAPPA reconstruction of simultaneous multislice EPI with slice‐dependent 2D Nyquist ghost correction

Abstract: Purpose To provide simultaneous multislice (SMS) EPI reconstruction with k‐space implementation and robust Nyquist ghost correction. Methods 2D phase error correction SENSE (PEC‐SENSE) was recently developed for Nyquist ghost correction in SMS EPI reconstruction for which virtual coil simultaneous autocalibration and k‐space estimation (VC‐SAKE) was used to remove slice‐dependent Nyquist ghosts and intershot 2D phase variations in multi‐shot EPI reference scan. However, masking coil sensitivity maps to exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Structured low-rank matrix methods for EPI ghost correction (16)(17)(18)(19)(20) can be viewed as an extension of structured low-rank matrix methods for conventional MR image reconstruction (24,(28)(29)(30)(31)(32)(33)(34), and are based on the same underlying theoretical principles. In particular, it has been shown that when MRI images have limited support, smooth phase variations, multi-channel correlations, or transform-domain sparsity, then the MRI k-space data will be linearly predictable (35), which means that convolutional Hankel-or Toeplitz-structured matrices formed from the k-space data will possess low-rank characteristics.…”
Section: Background: Structured Low-rank Epi Ghost Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structured low-rank matrix methods for EPI ghost correction (16)(17)(18)(19)(20) can be viewed as an extension of structured low-rank matrix methods for conventional MR image reconstruction (24,(28)(29)(30)(31)(32)(33)(34), and are based on the same underlying theoretical principles. In particular, it has been shown that when MRI images have limited support, smooth phase variations, multi-channel correlations, or transform-domain sparsity, then the MRI k-space data will be linearly predictable (35), which means that convolutional Hankel-or Toeplitz-structured matrices formed from the k-space data will possess low-rank characteristics.…”
Section: Background: Structured Low-rank Epi Ghost Correctionmentioning
confidence: 99%
“…Nyquist ghosts are one of the most common EPI artifacts, and occur because of systematic differences between the interleaved lines of k-space that are acquired with different readout gradient polarities, and/or because of systematic differences between interleaved lines of k-space data that are acquired with different shots in a multi-shot acquisition. Despite substantial efforts over several decades to solve this problem (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), the widely-deployed modern ghost correction schemes are still prone to incomplete ghost suppression, as illustrated in Supporting Information Fig. S1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another class of high‐performance reference‐free EPI ghost correction methods have been proposed using low‐rank matrix completion approaches . Specifically, Lee et al used the annihilating filter‐based low‐rank Hankel matrix approach (ALOHA), where the key idea is to take advantage of the fact that the concatenated Hankel matrix, which consists of even and odd k‐space lines, has a low‐rank structure due to the multi‐channel redundancy.…”
Section: Introductionmentioning
confidence: 99%
“…17 Another class of high-performance reference-free EPI ghost correction methods have been proposed using low-rank matrix completion approaches. [19][20][21][22][23][24] Specifically, Lee et al 19 used the annihilating filter-based low-rank Hankel matrix approach (ALOHA), [25][26][27] where the key idea is to take advantage of the fact that the concatenated Hankel matrix, which consists of even and odd k-space lines, has a low-rank structure due to the multi-channel redundancy. Thus, the phase mismatch correction problem in EPI can be reformulated as a missing k-space interpolation problem for even and odd k-space data that can be solved using low-rank Hankel matrix completion.…”
Section: Introductionmentioning
confidence: 99%